A Conceptual Study of Charakokta Visha Vega and Chikitsa (AYUSHDHARA, 2024)
Whenever a person is exposed to Visha, it follows a course of Visha vega before causing the death of the person. Aim: To study the eight visha vega according to Acharya Charaka along with Veganusar chikitsa. Objective: To study different Dravya and Karma used during eight Visha vega management. Material & methods: For this review eight Visha vega will be analysed from the Charaka Samhita. For the study of Dravya used, Rasapanchaka and their corresponding pharmaceutical studies would be obtained from Dravyaguna text and CCRAS plant database, API, PubMed, Google Scholar, and Ayurvedic text. Discussion: Acharya Charaka mentioned 8 Vega of Visha or 8 stages of Visha along with their symptoms in each Vega and also their management in every Vega. Every Vega represents a Dhatu which visha enter by crossing over the respective kala with the force of Vayu as per Acharya Sushurta known as Vegantara. Also the symptoms in each Vega are of the Dhatu in which it resides and produces the symptoms according to its respective Dhatu. After analysing the Raspanchak of Dravya’s used during Vega most of the dominant Rasa was Tikta and Katu, Laghu ruksha guna, Katu vipaka and Ushna veerya respectively. Conclusion: After their Raspanchak evaluation it was concluded that the dominant Rasa was Tikta and Katu, Laghu ruksha guna, Katu vipaka and Ushna veerya. So it is can be said that the drugs used during treatment, are similar in properties to the Visha. These Dravya’s used possess the same potential similar to visha to fight against the Visha, so that it can reach the places where visha has been placed in the body and use in present times as per the complexities of visha. And the Hetuvipritarthkari chikista siddhant is also established in terms of Visha chikitsa.